Functional genetic variants of the IFN-λ3 (IL28B) gene and transcription factor interactions on its promoter. (June 2021) - Roy, Subhajit; Guha Roy, Debarati; Bhushan, Anand; Bharatiya, Seema; Chinnaswamy, Sreedhar
Abstract: Interferon lambda 3 (IFN-λ3 or IFNL3, formerly IL28B), a type III interferon, modulates immune responses during infection/inflammation. Several human studies have reported an association of single nucleotide polymorphisms (SNP) in the IFNL3 locus with expression level of IFNL3. Previous genetic studies, in the context of hepatitis C virus infections, had predicted three regulatory SNPs: rs4803219, rs28416813 and rs4803217 that could have functional/causal roles. Subsequent studies confirmed this prediction for rs28416813 and rs4803217. A dinucleotide TA-repeat variant (rs72258881) has also been reported to be regulating the IFN-λ3 promoter. In this study, we tested all these genetic variants using a sensitive reporter assay. We show that the minor/ancestral alleles of both rs28416813 and rs4803217, together have a strong inhibitory effect on reporter gene expression. We also show an interaction between the two principal transcription factors regulating IFNL3 promoter: IRF7 and NF-kB RelA/p65. We show that IRF7 and p65 physically interact with each other. By using a transient ChIP assay, we show that presence of p65 increases the promoter occupancy of IRF7, thereby leading to synergistic activation of the IFNL3 promoter. We reason that, in contrast to p65, a unique nature of IRF7 binding to its specific DNA sequence makes it more sensitive to changes in DNA phasing. As a result, we see that IRF7, but not p65-mediated transcriptional activity is affected by the phase changes introduced by the TA-repeat polymorphism. Overall, we see that three genetic variants: rs28416813, rs4803217 and rs72258881 could have functional roles in controlling IFNL3 gene expression.